Response to combination therapy of HCV 3a infected Pakistani patients and the role of NS5A protein - Iqbal Aqib (Virology Journal, 2011)
Abstract Background Hepatitis C virus (HCV) genotype 3a is known to show comparatively better response to combination therapy than genotype 1 and 4. Mutations within NS5A gene of HCV have earlier been implicated with response to interferon (IFN) therapies in chronic HCV patients among various populations. As response to therapy are available in different populations because of the ethnic and viral factors and there was no study available on the phenomenon of resistivity to IFN. Results Chronic HCV 3a infected Pakistani patients were kept on IFN-α and ribavirin therapy for six months. NS5A gene of HCV was amplified and sequenced in the case of all the patients prior to therapy and the sequences were analysed for mutations. Out of the total 27 patients, 20 (74.07%) were observed with sustained virological response (SVR), 4 (14.81%) patients were non responder (NR) while 3 (11.11%) patients exhibited in end of treatment response (ETR). Three (3/20) (15%) SVR patients and two (2/3) ETR patients had mutations (ranging from I-V amino acids) within the NS5A ISDR regions. While the rest of the SVR patients (85%) and the NR had no mutations at ISDR region when compared with HCV K3a ISDR. Conclusions Mutations within the NS5A gene of HCV 3a genotype may not influence the outcome of combination therapy in Pakistani populations.